Pyridoxal kinase inhibition by artemisinins down-regulates inhibitory neurotransmission - Kasaragod, Vikram Babu; Pacios-Michelena, Anabel; Schaefer, Natascha; Zheng, Fang; Bader, Nicole; Alzheimer, Christian; Villmann, Carmen; Schindelin, Hermann (Proceedings of the National Academy of Sciences of the United States of America, 2020)
The antimalarial artemisinins have also been implicated in the regulation of various cellular pathways including immunomodulation of cancers and regulation of pancreatic cell signaling in mammals. Despite their widespread application, the cellular specificities and molecular mechanisms of target recognition by artemisinins remain poorly characterized. We recently demonstrated how these drugs modulate inhibitory postsynaptic signaling by direct binding to the postsynaptic scaffolding protein gephyrin. Here, we report the crystal structure of the central metabolic enzyme pyridoxal kinase (PDXK), which catalyzes the production of the active form of vitamin B6 (also known as pyridoxal 5'-phosphate [PLP]), in complex with artesunate at 2.4-A resolution. Partially overlapping binding of artemisinins with the substrate pyridoxal inhibits PLP biosynthesis as demonstrated by kinetic measurements. Electrophysiological recordings from hippocampal slices and activity measurements of glutamic acid decarboxylase (GAD), a PLP-dependent enzyme synthesizing the neurotransmitter gamma-aminobutyric acid (GABA), define how artemisinins also interfere presynaptically with GABAergic signaling. Our data provide a comprehensive picture of artemisinin-induced effects on inhibitory signaling in the brain.
CRIS-Team WoS Importer:2021-01-22